(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In today’s period of large-scale socio-economic and geopolitical changes, the growth and development of cities is accelerating, and the role and importance of the extremely complex and vibrant urbanization process in the life of society is increasing and expanding day by day. Therefore, a comprehensive study of this process is not only from a theoretical point of view, but also some regional and global practical issues, including the territorial composition of the population and its scattered, located settlements, and the most important and large-scale task - problems related to improving the territorial organization of society. necessary in solving.